Hazards and Risks Identification in Swimming Activities at the Oya River - Raihan Bagas Prabadika; Machfudz Eko Arianto (Universitas Ahmad Dahlan, 2025)
Background: Accidents in tourist attractions are very common, especially in natural tourism. Many factors can affect incidents at tourist attractions, whether they are factors from visitors, managers, safety facilities, or tourist locations. In 2023, there were 2 tourists who drowned because they were dragged by the flow of the Oya River in Kapanewon Imogiri, Bantul. As a result of the incident, several tourist attractions around it were temporarily closed to evaluate tourism management. For this reason, it is necessary to identify tourist safety hazards and risks. The purpose of this study is to identify the dangers and risks of swimming activities in the Oya River. Methods: this study uses a qualitative method with a descriptive type of research and uses a case study approach. The number of informants in this study amounted to 4 people consisting of 1 tourism manager, 1 land owner, and 2 tourists. Results: The results of the study show that there are types of hazards in the Kedung Parangan tourist attraction, namely gravity hazards, movement hazards, biological hazards, temperature hazards, and radiation hazards. The results of the risk assessment carried out using the risk table obtained results for all tourism activities, namely 16 low risk levels, 1 medium risk level and 1 high risk level. Conclusion: The potential danger that has a high level of risk is found in the potential danger of underheating that is at risk of cramping.